The Impact of ESG Practices on Corporate Performance in the Context of Digital Transformation: A Case Study of TBEA - Wang, Jie; Zeng, Xiangfeng (International Journal of Global Economics and Management, 2024)
In the context of digital transformation, enterprises are facing unprecedented opportunities and challenges, and environmental, social, and governance (ESG) practices have gradually become a focus of attention for enterprises. How to improve their own ESG practices to enhance corporate performance is crucial for the sustainable development of enterprises. This article selects TBEA as a case study enterprise to study its ESG practices from the perspectives of environment, society, and corporate governance in the context of digital transformation. Furthermore, relevant indicators are used to analyze the impact of ESG practices on corporate performance. Research has found that good ESG practices can promote the improvement of a company's financial and non-financial performance, with non-financial performance mainly reflected in the value created by the company for stakeholders.